How comprehensive are nuclear medicine residency websites? - Taylor Plas; Sherwin Novin; Paul Yi (World Journal of Nuclear Medicine)
Our goal for this study was to evaluate the comprehensiveness of nuclear medicine (NM) residency websites from the USA and Canada. The authors searched all the existing NM residency programs as listed in the Fellowship and Residency Electronic Interactive Database and the Canadian Residency Matching Service. We analyzed each website for the presence or absence of 44 elements previously identified as important considerations for medical students applying to residency. We compared criteria prevalence between regions and program size using t-tests and analysis of variance. Our results showed that, of 47 NM residencies, 9 did not have a dedicated website, leaving a total of 38 websites available for evaluation. The individual websites in the USA had a mean of 15 of 44 elements sought; in contrast, Canadian programs had 26 of 44 elements sought. The most common elements included contact e-mail, mailing address, and comprehensive faculty listings. Information about resident hometown, academic interests, and extracurricular interests was only included in 3% of the websites. Only 3% of websites included case description and 11% included rotation schedule. Courses attended were included in 5%, educational resources in 8%, and resident education was included in 5% of the websites. In conclusion, about one in five NM residency programs do not have a publicly available website. The websites that do exist are incomprehensive, containing an average of only 32% of elements sought for the USA programs and 41% of elements sought in Canadian programs. Residency program websites are an important tool in recruiting medical students. Addressing the lack of available websites as well as the gap in content of the websites that does exist may improve recruitment of students to NM residency programs.